ISOLASI SENYAWA ALKALOID DARI EKSTRAK METANOL DAGING BUAH Tabernaemontana macrocarpa Jack - Wulandari, Adisti Riska; Alimuddin, Andi Hairil; Rudiyansyah, Rudiyansyah (Tanjungpura University, 2024)
The community has used Tabernaemontana macrocarpa Jack for traditional medicinal purposes such as toothaches, herpes, scabies, and also as poison on arrowheads. This research aims to isolate and characterize the structure of alkaloid compounds in the methanol extract of Tabernaemontana macrocarpa Jack. Extraction was carried out through maceration using methanol as the solvent. The methanol extract was partitioned using n-hexane, dichloromethane, and ethyl acetate. Fractionation was performed using gravity column chromatography, where silica gel was employed as the stationary phase, and a mixture of n-hexane-dichloromethane and dichloromethane-methanol with increasing polarity was used as the mobile phase. At this stage, nine combined fractions were obtained. Fractions that tested positive for alkaloid compounds were further separated using the preparative TLC method. The resulting isolate was a light yellow powder weighing 4 mg. The isolated compound was further characterized using 1H-NMR spectroscopy. The analysis results from the 1H-NMR spectrum suggest that the isolate is an indole alkaloid compound. Based on the 1H-NMR data, the isolate from fraction seven exhibited chemical shift values consistent with those of taberniacin, an indole alkaloid previously reported from Tabernaemontana divaricata.